Dietary Factors and Supplements Influencing Prostate-Specific Antigen (PSA) Concentrations in Men with Prostate Cancer and Increased Cancer Risk: An Evidence Analysis Review Based on Randomized Controlled Trials - Grammatikopoulou, Maria G. (Nutrients, 2020)
The quest for dietary patterns and supplements efficient in down-regulating prostate-specific antigen (PSA) concentrations among men with prostate cancer (PCa) or increased PCa risk has been long. Several antioxidants, including lycopene, selenium, curcumin, coenzyme Q10, phytoestrogens (including isoflavones and flavonoids), green tea catechins, cernitin, vitamins (C, E, D) and multivitamins, medicinal mushrooms (Ganoderma lucidum), fruit extracts (saw palmetto, cranberries, pomegranate), walnuts and fatty acids, as well as combined supplementations of all, have been examined in randomized controlled trials (RCTs) in humans, on the primary, secondary, and tertiary PCa prevention level. Despite the plethora of trials and the variety of examined interventions, the evidence supporting the efficacy of most dietary factors appears inadequate to recommend their use.